Developing a Framework for Objective Structured Clinical Examinations Using the Nominal Group Technique - Hussainy, Safeera Y. (Am J Pharm Educ, 2016)
Objective. To use the nominal group technique to develop a framework to improve existing and develop new objective structured clinical examinations (OSCEs) within a four-year bachelor of pharmacy course. Design. Using the nominal group technique, a unique method of group interview that combines qualitative and quantitative data collection, focus groups were conducted with faculty members, practicing pharmacists, and undergraduate pharmacy students. Five draft OSCEs frameworks were suggested and participants were asked to generate new framework ideas. Assessment. Two focus groups (n=9 and n=7) generated nine extra frameworks. Two of these frameworks, one from each focus group, ranked highest (mean scores of 4.4 and 4.1 on a 5-point scale) and were similar in nature. The project team used these two frameworks to produce the final framework, which includes an OSCE in every year of the course, earlier implementation of teaching OSCEs, and the use of independent simulated patients who are not examiners. Conclusions. The new OSCE framework provides a consistent structure from course entry to exit and ensures graduates meet internship requirements.